2022
DOI: 10.1002/cpp.2800
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the research priorities for schema therapy: A Delphi consensus study

Abstract: Despite the popularity of schema therapy, there exist several important gaps in research on the schema therapy model and its effectiveness. The number of gaps makes it difficult to determine the research areas of the highest strategic priority to advance schema therapy. The objective of this study was to establish consensus among schema therapy clinicians and researchers on the priority areas for future schema therapy research. A panel of experts in schema therapy (43 clinicians and 13 researchers) participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…These findings converge with insights from the Delphi consensus study (Pilkington et al, 2023), which indicated that schema therapy Furthermore, our bibliometric analysis did not evidence much in the way of experimental studies. Given that the schema therapy model assumes that EMSs are activated across a wide variety of contexts it may also be beneficial for the field to invest in the design and conduct of studies with an experimental focus.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings converge with insights from the Delphi consensus study (Pilkington et al, 2023), which indicated that schema therapy Furthermore, our bibliometric analysis did not evidence much in the way of experimental studies. Given that the schema therapy model assumes that EMSs are activated across a wide variety of contexts it may also be beneficial for the field to invest in the design and conduct of studies with an experimental focus.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, authorship analyses identified several clusters of key collaborators in the field. In the sections that follow, we discuss these findings in detail, highlight where they converge with the findings of the Delphi consensus study on the priorities for future schema therapy research (Pilkington et al, 2023) and outline the implications for research and practice.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Unmeasured differences in coping may also contribute to the between‐study variation in the strength of the reported associations. Despite the centrality of coping styles and responses to the schema therapy model, few studies have examined the inter‐relationships between coping, emotion regulation processes, and EMSs (Pilkington et al, 2023). This warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%